Portable neonatus incubator based on global positioning system - Salahuddin, Nur Sultan; Sari, Sri Peornomo; Musyaffa, Aqilla Rahman (International Journal of Reconfigurable and Embedded Systems (IJRES), 2024)
The role of baby incubator is crucial in assisting premature babies to adjust to their new surroundings. However, the current baby incubator causes challenges when used for emergency first aid. The challenge is often because of its cumbersome size, which makes transportation to referral hospitals difficult. To address this issue, portable neonate incubator based on the global positioning system (GPS) was developed. The results of implementation testing showed that the incubator system effectively monitored longitude and latitude coordinates, as well as the temperature and humidity of the incubator room, and the body temperature of neonates. Weighing approximately 5.8 kg, this incubator was versatile, compatible with both AC and DC voltage power sources, and came equipped with a carrying bag for easy transportation by midwives or medical personnel. Consequently, this development marked an innovative advancement in neonate incubator medical equipment, facilitating the swift tracking of the neonate incubator's coordinate position in case of unexpected events on the way to the hospital.